EVALUASI KINERJA REKSA DANA SYARIAH: STUDI KASUS PASAR MODAL SYARIAH INDONESIA - Abdurrohman Akbar, Firman Muhammad; Rosidta, Adina; Lazuardi, Afried (An Nawawi, 2023)
This study examines the performance evaluation of Islamic mutual funds in the context of the Indonesian Sharia capital market. Islamic mutual funds are investment instruments that offer attractive alternatives for Muslim investors who wish to participate in the capital market while adhering to Islamic financial principles. In this study, a qualitative research methodology with a case study approach was employed to analyze the performance of Islamic mutual funds in the Indonesian Sharia capital market. The research involved an in-depth analysis of factors influencing the performance of Islamic mutual funds, such as historical performance, associated risks, portfolio characteristics, fund management, and compliance with Sharia principles. The findings of this study indicate that Islamic mutual funds in the Indonesian Sharia capital market have experienced significant growth during the research period from 2019 to May 2023. Although the growth in the number of Islamic mutual funds has been relatively slow, it reflects the increasing interest of investors in investment instruments that align with Sharia principles